Supervising for success : a guide for supervisors - Moglia, Tony (Crisp Pub Menlo ParkUS, 1997)
Defines the supervisor's role and discusses the attitude and image of the supervisor. Examines the human skills necessary for team building; and suggests the following strategies for getting work done: delegation; expeditious decision-making; and planning ahead.